Cet autre regard du portrait - Bernier, Christine (Ciel variable)

(untitled) (Les Productions Ciel variable, 2004)
Abstract Pascal Grandmaison's photographic and videographic work is often defined as renewing the concept of the portrait. This text explains that the innovation of Grandmaison's portraits is situated more in the layout of his exhibitions than in the modes of representation that he uses. Some characteristics of his portraits, such as the static pose and the absence of expression in the subject's regard, correspond to definitions of the traditional portrait. On the other hand, the presentation of Grandmaison's works makes use of the specular, repetition, and empty space, creating a unique relationship between the viewer and the portrait.